أثر القيادة الأخلاقية على أساليب إدارة الانطباع دراسة ميدانية في الشركة الوطنية للكهرباء والغاز سونلغاز بتقرت - مزهوده, نورالدين; بوخلوة, باديس (جامعة الوادي - University of Eloued, 2021)
This study aims to highlight the effect of ethical leadership on impression management styles in SONALGAZ company in Touggourt, where the descriptive and analytical method was relied on to highlight the concepts related to the subject of study, analyse them and extrapolate the results, and in order to achieve the objectives of the study, the questionnaire was designed that included 30 items to collect the primary information, as 75 questionnaires were processed by the statistical program SPSS V26, and using many statistical methods, including arithmetic averages, correlation, coefficient and linear regression. And the study reached a set of results, that ethical leadership is practiced in company at a high level, the prevailing style of impression management In the company is self reinforcement, and there is an effect of ethical leadership on impression management styles.
The effect of ethical leadership on impression management styles Applied study in The National Electricity and Gaz Company SONALGAZ Touggourt
مقال
Keywords: قيادة أخلاقية، أساليب إدارة الانطباع، شركة وطنية للكهرباء والغاز سونلغاز